The Effect of Soy Isoflavones on Steroid Metabolism - Swart, Amanda C.; Johannes, Inge D.; Sathyapalan, Thozhukat; Atkin, Stephen L. (Frontiers in Endocrinology, 2019)
Objective: This study is a post hoc analysis of steroid hormones before and after administration of pharmacological doses of soy isoflavones in a large cohort of men and women from two independent studies. Isoflavones are reported to inhibit mineralo- and glucocorticoid hormone production as well as reproductive steroids in vivo and in vitro. We focused on cytochrome P450 17α-hydroxylase (CYP17A1) which catalyses the production of dehydroepiandrosterone (DHEA), in the androgen biosynthesis pathway to elucidate effects on sex steroids in vitro. Design and Setting: Effects of soy isoflavones on steroid levels in two studies comprising 400 patients were examined: 200 men (termed, “Men study”; 3 months duration) and 200 postmenopausal women (termed, “Women study”; 6 months duration), randomized to consume 15 g soy protein with 66mg isoflavones (SPI) or 15 g soy protein alone without isoflavones (SP) daily. Effects of genistein and daidzein on steroid metabolism were determined in vitro, in HEK293 cells expressing CYP17A1 and in the human adrenocortical carcinoma H295R cell model. Results. SPI decreased serum dehydroepiandrosterone sulfate (DHEAS) levels in both men and women (P<0.01), with decreased androstenedione (A4) (P<0.01) in women not observed in men (P<0.86). Cortisol, cortisone, 11-deoxycortisol, aldosterone, testosterone (T) or estradiol (E2) levels were unchanged. The dual hydroxylase and lyase activity of CYP17A1, which catalyses the biosynthesis of androgen precursors, and 3β-hydroxysteroid dehydrogenase (3βHSD2) were investigated in vitro. In transiently transfected HEK293 cells, only the lyase activity was inhibited by both genistein, 20% (P<0.001) and daidzein, 58% (P<0.0001). In forskolin-stimulated H295R cells DHEA production was decreased by daidzein (P<0.05) and genistein, confirming inhibition of the lyase activity by the isoflavones. Conclusion. In vivo clinical data suggested inhibition of CYP17A1 17,20 lyase within the adrenal in men and within the ovary and adrenal in females. This was confirmed in vitro with inhibition of the lyase activity by both genistein and daidzein. In addition, 3βHSD2 was inhibited perhaps accounting for decreased A4 levels observed in females. The decreased DHEAS and A4 levels together with the inhibition of the 17,20 lyase activity of CYP17A1,